Efektivitas Pengolahan Air Limbah Grey Water Menggunakan Metode Lahan Basah Buatan Dengan Aliran Vertical Subsurface Flow (LBB-AVSSF) - Nevy Amirda Oktavia; Rudy Yoga Lesmana; Putro, Dhymas Sulistyono (BIOMARAS : Journal of Life Science and Technology, 2024)
Domestic wastewater is wastewater originating from businesses and/or residential activities (real estate), restaurants, offices, commerce, apartments and dormitories. Based on its characteristics, there are 2 types of domestic wastewater, namely black water comes from toilets and is generally collected in septic tanks, while gray water comes from washing, bathing and cooking activities, which is generally discharged directly into drainage channels or public waters without undergoing prior processing. One alternative recommended to overcome this problem is the vertical sub-surface flow artificial wetland method. This research aims to determine the effectiveness of the vertical sub-surface flow artificial wetland method in treating gray water wastewater with apu wood plants (Pistia Stratoites) in reducing pollutant levels. Artificial wetlands are created using gravel and sand on a laboratory scale. Data analysis was carried out based on the results obtained from analysis of pH, BOD, COD and Ammonia parameters before and after processing. Detention times 3, 6, and 9 as treatment days. The main parameters are Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and ammonia. Supporting parameters pH and temperature. Artificial wetlands have proven to be very effective in treating gray water wastewater with apu wood plants (Pistia Stratoites) as a reducing medium. The research results showed that efficiency occurred at a detention time of 3 days by reducing BOD levels by 98.33%, COD by 98.42% and ammonia by 92.22%. The results of this research have met the requirements set by the Minister of Environment and Forestry Regulation No: P. 68/Menlhk/Setjen/Kum.1/8/2016 concerning Domestic Wastewater Quality Standards.